Pharmacoeconomic aspects related to the 13-valent pneumococcal conjugate vaccine: preliminary analysis of the data from the ASL of Viterbo - Dari, Silvia; Verginelli, Flavia; Aquilani, Silvia (Farmeconomia. Health economics and therapeutic pathways, 2014)
INTRODUCTION: Streptococcus pneumoniae is a pathogen of considerable importance to public health because it causes morbidity and mortality on the world population. It has more than 90 serotypes with different epidemiological characteristics and pathogenicity. Some categories of the population are particularly vulnerable to infection. The Regional Plan for the Prevention of Lazio for vaccination, based on the national plan for the prevention for vaccination involves the active offer of vaccination no 13-valent PCV, with a target of at least 90% in children 24 months of age. OBJECTIVE: To begin to assess the real economic impact of disease attributable to Pneumococcus, starting from the analysis of hospital discharge records (SDO) of the Viterbo's ASL. METHODS: The model is structured follows the observational approach of 33 months, from January 2012 to September 2014, selecting the SDO with a principal diagnosis of Streptococcus Pneumoniae diseases and those with a principal diagnosis of respiratory diseases without etiological diagnosis, which, with good approximation, it can be considered responsible for Streptococcus pneumoniae 40%. RESULTS: From the preliminary analysis of the data, evaluating only patients diagnosed due to Pneumococcus, is known as the only pediatric cases hospitalized are between 0 and 1 year. Therefore one might assume that vaccination disbursed to the child population with 13-valent PCV, has ensured effective protection to persons of the age group 2-18 years. CONCLUSIONS: The importance of this study is the observation conducted on an ASL, (similar in size and catchment area to many Italian realty) of the vaccination coverage effects, as provided by PRPV Lazio Region, on hospitalizations by Pneumococcus. The study offers a moment of reflection for decision makers, as it would be interesting to conduct pharmacoeconomic’s analysis in the presence of vaccination strategies extended to adults, especially for those at risk, associated with diagnostic tests etiological more specific.